Determinant Factors in Improving the Quality of E-Government-Based Health Public Services at Syech Yusuf Hospital, Gowa Regency - Djamaluddin, Musdalifah; Akib, Haedar; Anshari, Anshari (Darul Yasin Al Sys, 2025)
Health services are one of the important aspects of public services that aim to improve the welfare of the community. This research focuses on the quality of e-government-based health services at RSUD Sheikh Yusuf Gowa Regency, which has implemented information technology innovations such as SIMRS and Mobile JKN applications. Despite efforts to improve efficiency and public satisfaction, various obstacles remain, such as limited human resources, infrastructure, information systems, and suboptimal coordination between units. Using a descriptive qualitative approach, this study explores the determinants that affect service delivery, both enabling factors such as the competence of medical personnel, adequate facilities and infrastructure, and information technology, as well as inhibiting factors such as complicated bureaucracy, lack of digital literacy, and limited employee motivation. The results indicate the need for comprehensive improvements, including strengthening the capacity of human resources, simplifying procedures, improving facilities, and optimizing technology to improve the quality of health services. The findings are expected to serve as a basis for RSUD Sheikh Yusuf in providing better quality, efficient services that meet the expectations of the community.